Stochastic power spectra models for typhoon and non-typhoon winds: A data-driven algorithm - Liu, Zihang; Fang, Genshen; Hu, Xiaonong; Xu, Kun; Zhao, Lin; Ge, Yaojun (Journal of wind engineering and industrial aerodynamics, 2022)
The shape of power spectra both for typhoon and non-typhoon winds directly affect the response level of the structure. The conventional deterministic spectrum models fail to reproduce the randomness of the structure response and could underestimate the real vibration amplitudes, especially for typhoon winds featured with stronger gustiness due to internal circulation and thermodynamic effects. Based on long-term observation data captured by the structural health monitoring system installed at Xihoumen suspension bridge, the parameters of wind power spectra in along-wind, cross-wind and vertical directions for typhoon and non-typhoon winds are extracted, respectively. The statistical characteristics and correlations among these parameters are examined. The data-driven stochastic power spectra models are then proposed by utilizing the moment-based theoretical solutions and Monte Carlo technique, respectively. The mean wind speed is incorporated in these models which allows the random simulations of power spectra with respect to different mean wind speeds. The proposed stochastic model is finally applied to generate a large number of wind power spectra adapted to the mean extreme wind speed return period curves in typhoon and non-typhoon mixed climates. It is suggested that the present stochastic power spectra model can be applied to estimate the random response of structures at different return periods due to typhoon and non-typhoon winds, which can be extended to conduct the performance-based design and uniform-risk-based design of structures in wind engineering. •Highlights (for review).•Stochastic power spectra models of typhoon and non-typhoon wind are developed using moment-based and Monte-Carlo methods.•Statistical characteristics and correlations among wind power spectra parameters and mean wind speed are examined.•Stochastic power spectra models allow the random simulations of spectra with respect to different mean wind speeds.•Connection between mean wind speed and power spectra allows predicting structure response at different return periods.